Quantifying surface‐area changes of volcanic islands driven by Pleistocene sea‐level cycles: biogeographical implications for the Macaronesian archipelagos. (22nd May 2014) - Rijsdijk, Kenneth F.; Hengl, Tom; Norder, Sietze J.; Otto, Rüdiger; Emerson, Brent C.; Ávila, Sérgio P.; López, Heriberto; van Loon, E. Emiel; Tjørve, Even; Fernández‐Palacios, José María; Heaney, Lawrence
Abstract Aim We assessed the biogeographical implications of Pleistocene sea‐level fluctuations on the surface area of Macaronesian volcanic oceanic islands. We quantified the effects of sea‐level cycles on surface area over 1000‐year intervals. Using data from the Canarian archipelago, we tested whether changes in island configuration since the late Pleistocene explain species distribution patterns. Location Thirty‐one islands of four Macaronesian archipelagos (the Azores, Madeira, the Canary Islands and Cape Verde). Methods We present a model that quantifies the surface‐area change of volcanic islands driven by fluctuations in mean sea level (MSL). We assessed statistically whether Canarian islands that were merged during sea‐level lowstands exhibit a significantly higher percentage of shared (endemic) species than other comparable neighbouring islands that remained isolated, using multimodel comparisons evaluated using the Akaike information criterion (AIC). Results Each Macaronesian island exhibited a unique area‐change history. The previously connected islands of Lanzarote and Fuerteventura share significantly more species of Insecta than the similarly geographically proximate island pair of La Gomera and Tenerife, which have never been connected. Additionally, Lanzarote and Fuerteventura contain the highest percentage of two‐island endemic Plantae species compared with all other neighbouring island pairs within the Canaries. The multimodel comparison showed that past connectedness provides improved explanatory models of shared island endemics. Main conclusions Pleistocene sea‐level changes resulted in abrupt alterations in island surface areas, coastal habitats and geographical isolation, often within two millennia. The merging of currently isolated islands during marine lowstands may explain both shared species richness and patterns of endemism on volcanic islands. Currently, the islands are close to their long‐term minimum surface areas and most isolated configurations, suggesting that insular biota are particularly vulnerable to increasing human impact.